Phytochemical Investigation of Egyptian Riverhemp: A Potential Source of Antileukemic Metabolites - Shimaa M. Abdelgawad; Mona H. Hetta; Mohamed A. Ibrahim; Premalatha Balachandran; Jin Zhang; Mei Wang; Wagdy M. Eldehna; Ghada A. Fawzy; Hesham I. El-Askary; Samir A. Ross (Journal of Chemistry)
As part of our research group’s continuous efforts to find alternative treatments for cancer, the aqueous ethanol extract of Sesbania sesban L. Merr. (SS, Egyptian riverhemp) demonstrated an antileukemic activity against K562 cell line. Bioguided fractionation of SS leaves hydroethanolic extract resulted in the isolation of one new compound (33) named as hederatriol 3-O-β-D-glucuronic acid methyl ester as well as 34 known compounds. Seven compounds ((34), (22), (20), (24), (21), (19), and (35)) showed high antiproliferative effects (IC50 = 22.3, 30.8, 31.3, 33.7, 36.6, 37.5, and 41.5 μM, respectively), while four compounds ((32), (5), (29), and (1)) showed milder activities (IC50 = 56.4, 67.6, 83.3, and 112.3 μM, respectively). A mechanistic study was further carried out on a molecular genetics level against several transcription factors signaling pathways that are incorporated in the incidence of cancer. The results showed that compounds (22) and (21) demonstrated a specific inhibition of Wnt pathway (IC50 = 3.8 and 4.6 μM, respectively), while compound (22) showed a specific inhibition of Smad pathway (IC50 = 3.8 μM). Compound (34) strongly altered the signaling of Smad and E2F pathways (IC50 = 5 μM). The bioactive metabolites were further investigated in silico by docking against several targets related to K562 cell line. The results showed that compounds (22) and (34) exhibited a strong binding affinity towards topoisomerase (docking score = −7.81 and −9.30 Kcal/Mole, respectively). Compounds (22) and (34) demonstrated a strong binding affinity towards EGFR-tyrosine kinase (docking score = −7.12 and −7.35 Kcal/Mole, respectively). Moreover, compound (34) showed a strong binding affinity towards Abl kinase (docking score = −7.05 Kcal/Mole).